Pietermaritzburg in the Great War : corporate patriotism and civic sacrifice (Historia, 2021)
The city of Pietermaritzburg was the capital of the South African province of Natal. The white polity was predominantly English in background and sentiment, and its response to the declaration of war was enthusiastically pro-British. This article is an account of the corporation's war effort and the civic sacrifices it entailed. The town council consistently supported the imperial cause, and the corporation encouraged staff to volunteer for military service, making generous allowances for them and their families. Patriotic organisations were established to promote volunteering, to raise funds for war relief, and to provide aid and comforts to the troops. Local women played an important role in fundraising and aid and comforts. By the end of the first year of the war, these activities were regularised and patriotic observances were ritualised. Patriotism did not falter, but by 1916 morale was strained by mounting casualties at the front and shortages and inflation at home. By 1918 war weariness could not be concealed and local authorities were searching for new ways to sustain popular morale. The response to the announcement of the armistice was enthusiastically British, but tinged with profound relief and gratitude.  Die stad Pietermaritzburg was die hoofstad van die Suid-Afrikaanse provinsie van Natal. Die wit politieke bestel was agtergrond- en sentimentgewys oorheersend Engels, en die reaksie daarvan op die oorlogsverklaring was geesdriftig pro-Brits. Hierdie artikel rekenskap van die korporasie se oorlogspoging en die burgerlike opofferings wat dit ingehou. Die Stadsraad het konsekwent die imperiale beweegrede ondersteun, en die korporasie het die personeel aangemoedig om vrywillig vir militêre diens aan te meld, terwyl dit milde toelae aan hulle en hul families voorsien het. Patriotiese organisasies is tot stand gebring om vrywillige diens te bevorder, om fondse vir noodleniging in te samel en hulpmiddele en geriewe aan die troepe te voorsien. Plaaslike vroue het 'n belangrike rol met betrekking tot fondsinsameling en hulpmiddele en geriewe vervul. Teen die einde van die eerste oorlogsjaar is hierdie aktiwiteite gereguleer en patriotiese handhawing verwesenlik. Patriotisme het nie gewankel nie, maar teen 1916 was die moreel getap weens toenemende ongevalle op die front en tekorte en inflasie tuis. Teen 1918 kon oorloguitputting nie langer verberg word nie en plaaslike owerhede het begin soek na nuwe maniere om volksmoreel te handhaaf. Die reaksie op die aankondiging van die wapenstilstand was geesdriftig Brits, maar met diepe verligting en dankbaarheid.
Keywords: Britse imperiale patriotisme; First World War; Dominion patriotism; Pietermaritzburg; Great War